2008
DOI: 10.1016/j.foodcont.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of natural antimicrobials and high pressure processing to prevent Listeria monocytogenes growth after a cold chain break during storage of cooked ham

Abstract: 1The effect of high pressure processing (400 MPa for 10 min) and natural antimicrobials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 24 publications
(27 reference statements)
1
52
1
3
Order By: Relevance
“…The antilisterial activity of enterocins immobilised in plastic interleaves was strongly potentiated by application of HHP treatment (400 MPa, 10 min), reducing viable counts by about 4 log units and holding the levels of L. monocytogenes in the treated sliced ham below 1.5 log CFU/g at the end of storage for 30 days at 6 °C (Jofré et al 2007 ). Storage of samples at a lower temperature of 1 °C extended the protective effect of the combined treatment for at least 60 °C, even in the event of a simulated cold chain break ( Marcos et al 2008b ). In a separate study (Marcos et al 2008a ), sliced cooked ham was packaged in alginate fi lms containing or not enterocins A and B, and then was pressurized (400 MPa, 10 min, 17 °C).…”
Section: Semi-processed and Cooked Meatsmentioning
confidence: 99%
“…The antilisterial activity of enterocins immobilised in plastic interleaves was strongly potentiated by application of HHP treatment (400 MPa, 10 min), reducing viable counts by about 4 log units and holding the levels of L. monocytogenes in the treated sliced ham below 1.5 log CFU/g at the end of storage for 30 days at 6 °C (Jofré et al 2007 ). Storage of samples at a lower temperature of 1 °C extended the protective effect of the combined treatment for at least 60 °C, even in the event of a simulated cold chain break ( Marcos et al 2008b ). In a separate study (Marcos et al 2008a ), sliced cooked ham was packaged in alginate fi lms containing or not enterocins A and B, and then was pressurized (400 MPa, 10 min, 17 °C).…”
Section: Semi-processed and Cooked Meatsmentioning
confidence: 99%
“…Low water activity protects cells against pressure, but microorganisms injured by HP are generally more sensitive to low water activity (Cheftel and Culioli, 1997). The combined treatment of enterocins and lactate-diacetate, with HP treatment eliminated microorganisms inoculated on cooked ham (Marcos et al, 2008). Evrendilek and Balasubramaniam (2011) also reported that HP processing combined with mint essential oil appeared to be a promising technique for preserving microbiologically-safe yogurt with no significant impacts to product quality.…”
Section: A-dmentioning
confidence: 99%
“…High pressure processing (HP) is a non-thermal food preservation technology for inactivating post-processing contaminants, especially for foods whose nutritional, sensory and functional characteristics are thermo-sensitive (Marcos et al, 2008). HP kills and/or sub-lethally injures the cells by destroying the functionality of the cell wall and the cytoplasmic membrane, dissociating the proteins and the ribosomal subunit structures, and inactivating some enzymes (Hoover et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of preventing the deterioration and contamination of food, a number of conservation techniques are used, some of which incorporate additives, treatments with microorganisms, subjecting products to high pressure, drastic changes in temperature or cooling [5]. Of all of these tech-* * * VICTORIA RODRÍGUEZ / ITXASO AMORRORTU / MARÍA JESÚS ÁLVAREZ con-ciencias niques, cooling is the least aggressive in terms of how it affects the product [2].…”
Section: Theoretical Backgroundsmentioning
confidence: 99%